The role of zebrafish (Danio rerio) in dissecting the genetics and neural circuits of executive function - Parker, Matthew O.; Brock, Alistair J.; Walton, Robert T.; Brennan, Caroline H. (Frontiers in Neural Circuits, 2013)
Zebrafish have great potential to contribute to our understanding of behavioral genetics and thus to contribute to our understanding of the etiology of psychiatric disease. However, progress is dependent upon the rate at which behavioral assays addressing complex behavioral phenotypes are designed, reported and validated. Here we critically review existing behavioral assays with particular focus on the use of adult zebrafish to explore executive processes and phenotypes associated with human psychiatric disease. We outline the case for using zebrafish as models to study impulse control and attention, discussing the validity of applying extant rodent assays to zebrafish and evidence for the conservation of relevant neural circuits.